Etude in vitro d’une plante médicinale Algérienne ( Teucrium polium L) destinée au traitement d’appoint de plaies et de brûlures superficielle dans la médecine traditionnelle - BELAID, RANIA; BEZZEKKARA, KHEIRA (My University, 2024)
Medicinal plants and their components are potential new sources for the development of drugs against a variety of diseases. Teucrium polium L (germander), a member of the Lamiaceae family, is widespread in the dry, rocky areas of the hills and deserts of almost all Mediterranean countries. The aerial parts of Teucrium polium L (Lamiaceae), a wild-flowering plant, are widely used in traditional medicine to treat many illnesses, including abdominal pain, indigestion and type 2 diabetes. The aim of the present study was to evaluate the effect of different extraction solvents (ethanol, DES and distilled water) on the antioxidant capacity and total phenol , flavonoid and tanins contents of the aerial parts of Algerian Teucrium polium. The antioxidant capacity of Teucrium polium extracts was assessed by DPPH (2, 2-diphenyl-1-picrylhydrazyl) free radical scavenging tests. For each extract, total phenol , flavonoid and tannin contents were studied by the Folin-Ciocalteu, NaCO3 and aluminum trichloride methods respectively. These results show that all the extracts tested showed appreciable levels of total phenolic compounds, total flavonoids and total tannins, as well as high antioxidant capacity. The results of the quantitative analysis revealed the presence of polyphenols with a concentration of (0.012 and 0.084 mg/EAG) by the water bath extraction technique and(0.010 and 0.078mg/EAG) by the ultrasound extraction technique, flavonoids with (0, 005 and 0.046mg/EQ) according to the water bath extraction technique and (0.002 ±0.088mg/EQ) according to the ultrasound extraction technique, condensed tannins with a concentration of (1.327 ±0.014mg/EAT). The results show that the DPPH free radical method was used to assess the antioxidant power of the extracts. The results obtained showed a satisfactory antioxidant activity of the extract
Keywords: Antioxidant activity; Teucrium polium L; polyphenols; flavonoids and tanins